PENGARUH IKLAN TVC TIX ID VERSI”PENGABDI ZOMBIE” TERHADAP BRAND AWARENESS - Sungkono, Nono (JURNAL PUSTAKA KOMUNIKASI, 2019)
This study aims to find out 1) an evaluation of the TvC Tix ID Adverts for "Zombie Servants". 2) Brand Awareness on Tix Users ID 3) Effect of Tix ID TvC Ads on Brand Awareness. This study uses the theory of exposure to advertising, stimulus organism response, brand awareness and the AIDCA model. The type of research used is explanative. The research method used was survey. The research population from Tix ID Users at XXI Mall Blok M Plaza, South Jakarta with sampling techniques accidental sampling. The results of the study showed that the Evaluation of the TvC Tix ID Adverts for "Zombie Servants" refers to the three dimensions of Advertisements: Advertisements Frequency, Duration and Intensity. Brand Awareness TvC Tix ID Ads Version "Zombie Servants" in the eyes of Tix ID Users which refers to the three dimensions namely: Brand Recognition, Brand Recall, Top of Mind, then included in the category of Very Realizing. The magnitude of the influence of Tix ID TvC Ads on Brand Awareness, is known to include categories that have moderate influence.